Effect of Gender on Lung Function and Patient-Reported Outcomes in Patients with COPD Receiving Nebulized Glycopyrrolate - Ohar, Jill A (Int J Chron Obstruct Pulmon Dis, 2020)
PURPOSE: The clinical manifestation of COPD can differ by gender, with women experiencing worse lung function and health-related quality of life than men. Additionally, women tend to report more symptoms given the same disease severity. Accordingly, the impact of gender on efficacy and safety in patients with moderate-to-very-severe COPD was examined following 12 weeks of nebulized glycopyrrolate (GLY) 25 µg twice daily (BID) or placebo. PATIENTS AND METHODS: GLY and placebo pooled data from the replicate 12-week GOLDEN 3 and 4 studies (n=861) were grouped by gender. Endpoints reported were change from baseline in trough forced expiratory volume in 1 second (FEV(1)), St George’s Respiratory Questionnaire (SGRQ) and EXAcerbations of COPD Tool-Respiratory Symptoms (EXACT-RS) total scores. Safety was evaluated by reviewing the incidence of adverse events (AEs) and serious AEs. RESULTS: Men (placebo: 54.7%; GLY: 56.1%) were generally older with a greater proportion of high cardiovascular risk and use of background long-acting β(2)-agonists or inhaled corticosteroids. GLY treatment resulted in significant, clinically important improvements in trough FEV(1), regardless of gender. Patients treated with GLY reported significant improvements in SGRQ total score, irrespective of gender; however, the improvement was numerically higher in women. Although EXACT-RS improved in both genders, only women experienced a significant improvement. Overall, GLY was well tolerated with a numerically lower incidence of AEs in men than women. CONCLUSION: Treatment with nebulized GLY resulted in lung function, SGRQ total score, and EXACT-RS total score improvements regardless of gender. However, only EXACT-RS showed significantly greater improvements in women compared with men. Treatment with GLY was generally well tolerated across genders. These data support the efficacy and safety of GLY 25 µg BID in patients with moderate-to-very-severe COPD, independent of gender. Gender similarities in airflow improvement and differences in symptom-reporting augment the evidence supporting the consideration of individualized treatment plans for COPD patients.